sRNA-Mediated Regulation of P-Fimbriae Phase Variation in Uropathogenic Escherichia coli. - Surabhi Khandige; Tina Kronborg; Bernt Eric Uhlin; Jakob Møller-Jensen (PLoS Pathogens, 2015)
Uropathogenic Escherichia coli (UPEC) are capable of occupying physiologically distinct intracellular and extracellular niches within the urinary tract. This feat requires the timely regulation of gene expression and small RNAs (sRNAs) are known to mediate such rapid adjustments in response to changing environmental cues. This study aimed to uncover sRNA-mediated gene regulation in the UPEC strain UTI89, during infection of bladder epithelial cells. Hfq is an RNA chaperone known to facilitate and stabilize sRNA and target mRNA interactions with bacterial cells. The co-immunoprecipitation and high throughput RNA sequencing of Hfq bound sRNAs performed in this study, revealed distinct sRNA profiles in UPEC in the extracellular and intracellular environments. Our findings emphasize the importance of studying regulatory sRNAs in a biologically relevant niche. This strategy also led to the discovery of a novel virulence-associated trans-acting sRNA-PapR. Deletion of papR was found to enhance adhesion of UTI89 to both bladder and kidney cell lines in a manner independent of type-1 fimbriae. We demonstrate PapR mediated posttranscriptional repression of the P-fimbriae phase regulator gene papI and postulate a role for such regulation in fimbrial cross-talk at the population level in UPEC. Our results further implicate the Leucine responsive protein (LRP) as a transcriptional activator regulating PapR expression. Our study reports, for the first time, a role for sRNAs in regulation of P-fimbriae phase variation and emphasizes the importance of studying pathogenesis-specific sRNAs within a relevant biological niche.